Determination the Nosiocomial Infections among Burned Patients Admitted at Al-Husseini Teaching Hospital in Holy Karbala - Nada Khazal Kadhim Hindi (Journal of Global Pharma Technology, 2019)
Background: Burn injuries behold one of the most devastating injuries among people for all age in the worldwide leading to causes premature mortality and with the disability. Materials and Method: An Analytical and Descriptive Study Conducted in order to identify bacterial and associated bacterial types to burn exposure types and with a microbial location among 100 patients who were burned and who arrived at AL-Husseini Hospital Teaching/ Burn Department) were taken by swabs, equipment, nurse, and environment of hospital. Data was collected and analyzed through a descriptive and inferential statistics approach. Results: Most of the bacteria that transmitted to the burned patients were (Staphylococcus aureus) which causes burn nosocomial infections was isolated commonly from hands of nurses and equipment of patients. Patients were exposed significantly to the types of bacterial infection when the value of p detection <0.01. Also, the types of bacterial infection is associated with artificial to a large extent the location of bacteria isolated as the value of p <0.01. Conclusion: The study concluded that Staphylococcus aureus skin more bacteria in the hospital environment and medical staff, which can be infected with the patient, especially a patient who is under fire. Bacterial infections are associated with types of burns. Bacterial infection is also dependent on microbial infection. Confirmed our findings need for careful cleansing of patients and their surroundings.Keywords: Determination, Nosiocomial Infections, Burned Patients.